Evaluating herbicide resistance in Rumex spp. and its management in wheat (Triticum aestivum) - SUNIL, SUNIL; GARG, RAJBIR; SINGH, SAMUNDER; HARENDER, HARENDER; LOURA, DEEPAK (The Indian Journal of Agricultural Sciences, 2021)
Wheat (Triticum aestivum L.) crop grown with rice-wheat cropping system is infested with complex weed flora. Rumex spp. is the major broad-leaf weed of wheat crop wherein the poor efficacy of recommended herbicides and likelihood of herbicide resistance has been noticed. Hence, two herbicides - metsulfuron (X dose- 4g a.i/ha) and halauxifen + fluroxypyr (X dose- 240 g a.i/ha) applied at three doses (0.5X, X and 2.0X) were evaluated against four populations of Rumex spp. in a pot experiment carried out at screen house of college of Agriculture, CCS HAU, Hisar during rabi 2017-18. One unsprayed control was also kept for each population and herbicide for comparison. Results indicated that majority of the Rumex biotypes have attained resistance against metsulfuron and were not controlled even at double of the recommended dose. Higher values of plant height, chlorophyll fluorescence, fresh weight and dry weight and lower value of electrical conductivity was observed in the herbicidal treatments showing comparatively less efficacy against this weed. All Rumex biotypes were found highly sensitive to halauxifen + fluroxypyr at recommended dose and recorded 85-90% visual mortality. The application of halauxifen + fluroxypyr is the best alternative option to manage this weed in problematic areas.